2021
DOI: 10.1021/jacsau.1c00125
|View full text |Cite
|
Sign up to set email alerts
|

Single-Crystal Cobalt Phosphide Nanorods as a High-Performance Catalyst for Reductive Amination of Carbonyl Compounds

Abstract: The development of metal phosphide catalysts for organic synthesis is still in its early stages. Herein, we report the successful synthesis of single-crystal cobalt phosphide nanorods (Co 2 P NRs) containing coordinatively unsaturated Co–Co active sites, which serve as a new class of air-stable, highly active, and reusable heterogeneous catalysts for the reductive amination of carbonyl compounds. The Co 2 P NR catalyst showed high activity for the transformation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 48 publications
1
48
0
Order By: Relevance
“…Subsequently, 3a was converted to the desulfonylation product enone 5 following a perylene-catalyzed photodesulfonylation procedure. 22 Then, catalytic hydrogenation of alkene 5 led to the formation of dibenzocycloheptanone 6, which provided the allocolchicinoid 9 after cobalt phosphide nanorods (Co 2 P NRs) catalyzed reductive amination 23 followed by acetylation. Notably, though the reductive amination showed poor selectivity between amine 8 and alcohol 7 (7 was also formed in about 50% yield), 7 could be converted into ketone 6 by simple oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, 3a was converted to the desulfonylation product enone 5 following a perylene-catalyzed photodesulfonylation procedure. 22 Then, catalytic hydrogenation of alkene 5 led to the formation of dibenzocycloheptanone 6, which provided the allocolchicinoid 9 after cobalt phosphide nanorods (Co 2 P NRs) catalyzed reductive amination 23 followed by acetylation. Notably, though the reductive amination showed poor selectivity between amine 8 and alcohol 7 (7 was also formed in about 50% yield), 7 could be converted into ketone 6 by simple oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…In line with this, the alloying of non‐metal, such as phosphorous, has a positive role in stabilizing low valent metals like Co, thus enhancing hydrogenation capability by increasing the d‐electron density of the metal [82] . Recently, air‐stable single‐crystal cobalt phosphide nanorods have been developed for the reductive amination of benzaldehyde as a model substrate, with unsaturated Co−Co species as active sites (confirmed by FT‐EXAFS) [83] . Further, the activity of Co 2 P nanorods has been expanded to a broad range of carbonyl compounds (yielding 70–99 % corresponding amine), including FUR, producing 90 % FUA at 100 °C, 5 bar H 2 in aqueous ammonia.…”
Section: Reductive Amination With Ni and Co‐based Catalystsmentioning
confidence: 99%
“…[82] Recently, air-stable singlecrystal cobalt phosphide nanorods have been developed for the reductive amination of benzaldehyde as a model substrate, with unsaturated CoÀ Co species as active sites (confirmed by FT-EXAFS). [83] Further, the activity of Co 2 P nanorods has been expanded to a broad range of carbonyl compounds (yielding 70-99 % corresponding amine), including FUR, producing 90 % FUA at 100 °C, 5 bar H 2 in aqueous ammonia. The XANES spectrum of cobalt phosphide nanorods indicates the presence of Co species in a metallic state.…”
Section: Reductive Amination With Ni and Co-based Catalystsmentioning
confidence: 99%
“… 5 8 However, despite their unique properties the use of metal phosphide catalysts in organic syntheses has rarely been investigated. 9 13 Our group recently reported the unique catalytic properties exhibited by nonprecious metal phosphide (Ni 2 P and Co 2 P) NPs in selective liquid-phase molecular transformations, e.g., the transformation of biomass-derived molecules; 14 18 the hydrogenation of nitriles, carbonyls, nitroarenes, and sulfoxides; 19 22 the reductive amination of carbonyls; 23 and the alkylation of oxindoles. 24 These studies revealed the potential of nonprecious metal phosphide NPs to serve as a novel class of highly efficient heterogeneous catalysts for versatile liquid-phase reactions, outperforming conventional single nonprecious metal NPs.…”
Section: Introductionmentioning
confidence: 99%